The Dialectic of Reason and Text among Theologians and Philosophers: A Doctrinal Approach (Journal of the College of Basic Education, 2025)
Most theologians and philosophers attempted to establish a balance between reason and tradition, believing that the text should retain its referential status and reason its epistemic status. The Mu'tazilite theologians addressed the same issues of reason and textual interpretation as the philosophers. A review of Ibn Sina's philosophy reveals that he focuses on three fundamental elements for interpreting the text: language, philosophy, and Sufism. Language is a means to knowledge of the explicit meaning of the Quran, and he must turn to philosophy because the goal of interpretation is to uncover everything related to God, his essence, attributes, and actions. He should not be satisfied with transmitted evidence, but rather extend it to rational proofs. Because linguistic and philosophical sciences are deficient, this deficiency must be remedied by innate knowledge, which has no intermediary between the soul and God Almighty.The research problem:It lies in the following question: Did Muslim linguists, jurists, commentators, theologians, and philosophers all derive their work from an observation aimed at establishing a relationship between reason and tradition, out of a desire to preserve the text's referential status and reason its epistemological status? Or are reason and tradition merely two means to a single end, namely religious truth? Thus, religion and philosophy are combined in this topic.The importance of the topic and the reason for its selection:The importance of this study lies in the fact that the topic of reason and text is one of the most important and critical topics that emerged in the epistemological space of Islamic civilization. This is due to the complex nature of the topic, which touches upon the most specific characteristics of humanity (reason), as well as the most specific characteristics of religion (text). Therefore, the topic of reason and text among theologians and philosophers is a thorny and delicate topic around which all branches of knowledge produced by Islamic thought have revolved, whether this knowledge relates to language, jurisprudence, exegesis, Sufism, theology, or philosophy.Research objectives and hypothesis:The research aims to define the position of connection and separation, which sometimes reaches a position of complete rupture between theologians and philosophers. Theologians seek to innovate new perspectives on the subject, previously unseen in the approaches of philosophers. This became clear when theologians addressed an important doctrinal and legal issue, namely the dialectic of reason and text, in which philosophical discourse blended with the spirit of theology.